Factors influencing fatigue in Chinese nurses - Fang J. (2014)
Factors predicting fatigue in Chinese nurses were examined in a descriptive, correlational study. The participants were 581 nurses working in general hospitals in Chengdu City, China. The study instruments included the Occupational Fatigue Exhaustion Recovery Scale, the Job Content Questionnaire, the Exposure to Hazards in Hospital Work Environments Scale, the Pittsburgh Sleep Quality Index, the Job Dissatisfaction Scale, the Beck Anxiety Inventory, and the Beck Depression Inventory. The data were analyzed by using descriptive statistics, Pearson's correlation, F statistics, and multiple regression. The findings revealed that 61.7% of the variance in chronic fatigue and 54.9% of the variance in acute fatigue were explained by the independent variables. Intershift recovery was the most important variable in the explanation of acute fatigue, while acute fatigue was the most important variable in the explanation of chronic fatigue. Different intervention strategies should be implemented regarding the different influencing factors of acute and chronic fatigue. © 2008 The Authors Journal compilation © 2008 Blackwell Publishing Asia Pty Ltd.